Factors Associated with Intradiscal Vacuum Phenomenon after Traumatic Thoracolumbar Fracture - Sasagawa, Takeshi; Hayashi, Hiroyuki; Takagi, Yasutaka (Asian Journal of Neurosurgery, 2023)
Introduction Posttraumatic kyphosis of the thoracolumbar spine is a possible cause of deterioration of activities of daily living. Thus, postoperative kyphosis is an important issue in treating traumatic thoracolumbar fractures. The intradiscal vacuum phenomenon (IVP) after a traumatic thoracolumbar fracture is considered an important predictor of severe kyphosis after implant removal. However, the associated factors are not yet clear.Methods The study included data from 94 intervertebral discs on the cephalocaudal side of 47 fractured vertebrae of 45 patients for traumatic thoracolumbar fracture due to high-energy trauma. We assessed the demographics of patients (age, sex, cause of injury, location of injured vertebra, fracture type, cephalocaudal side), imaging finding (kyphosis angle of fractured vertebra at the injury, endplate fracture on computed tomography [CT], intervertebral injury on magnetic resonance image [MRI]), and IVP on CT conducted more than 6 months after surgery. We divided the intervertebral discs into an IVP group and a non-IVP group. To identify factors associated with an IVP, univariate analysis and multivariate logistic regression analysis were conducted.Results IVP was observed in 27 (29%) of 94 intervertebral discs on CTs conducted at an average of 14.0 months postoperatively. In univariate analysis, the IVP group (n = 27) had a significantly more cephalic side of the injured vertebra, endplate fracture on CT, and disc injury on MRI compared with the non-IVP group (n = 67). A multivariate logistic regression analysis was conducted to identify factors associated with IVP. The cephalic side (odds ratio [OR] = 4.183, 95% confidence interval [CI] = 1.269–13.785) and endplate fracture on CT (OR = 9.564, 95% CI = 1.940–47.143) were identified as independent factors associated with IVP.Conclusions IVP was observed in 27 (29%) of 94 intervertebral discs. The cephalic side and endplate fracture on CT were identified as independent factors associated with IVP.
Keywords: thoracolumbar fracture; intervertebral disc; degeneration; vacuum phenomenon; kyphosis; associated factor